Modelagem do impacto da taxa de reposição de matrizes nos aspectos produtivos de granjas de suínos - Muniz, Henrique da Costa Mendes (2023)
A simplified mathematical model of farms units producing weaned was developed, and two studies were conducted. The first study aimed to evaluate a deterministic mathematical model to predict the potential impacts of different sow replacement rates on the performance of units producing weaned. The second study assessed, through mathematical simulation, the influence of different female replacement rates on the quantity and cost of feed in units producing weaned. In the first study, it was concluded that the replacement gilt, gestation, and lactation modules developed in the model have the potential to predict the herd structure by parity order and evaluate the effects of the annual replacement rate of sows on the productivity of units producing weaned. The second study concluded that the replacement rate directly influences the structure of the herd and therefore the cost of feed within the weaning production units. Pointing to a lower cost with feed in the average economic scenario, for the replacement rate of 35% of the herd of a weaning production unit composed of 250 sows.